DNA methylation of NR3c1 in infancy: Associations between maternal caregiving and infant sex. Issue 4 (8th May 2019) - Conradt, Elisabeth; Ostlund, Brendan; Guerin, Dylan; Armstrong, David A.; Marsit, Carmen J.; Tronick, Edward; LaGasse, Lyn; Lester, Barry M.
ABSTRACT: Caregivers play a critical role in scaffolding infant stress reactivity and regulation, but the mechanisms by which this scaffolding occurs is unclear. Animal models strongly suggest that epigenetic processes, such as DNA methylation, are sensitive to caregiving behaviors and, in turn, offspring stress reactivity. We examined the direct effects of caregiving behaviors on DNA methylation in infants and infant stress reactivity. Infants and mothers ( N = 128) were assessed during a free play when infants were 5 months old. Maternal responsiveness and appropriate touch were coded. and infant buccal epithelial cells were sampled to assess for DNA methylation of the glucocorticoid receptor gene, NR3c1 exon 1F. Infant cortisol reactivity was assessed in response to the still‐face paradigm. Greater levels of maternal responsiveness and appropriate touch were related to less DNA methylation of specific regions in NR3c1 exon 1F, but only for females. There was no association with maternal responsiveness and appropriate touch or DNA methylation of NR3c1 exon 1F on prestress cortisol or cortisol reactivity. Our results are discussed in relation to programming models that implicate maternal care as an important factor in programing infant stress reactivity. RESUMEN: Los cuidadores juegan un papel esencial en el andamiaje de la reactividad y regulación del estrés infantil pero los mecanismos por medio de los cuales aparece este andamiaje no están claros. Los modelos animales fuertemente sugieren que los procesos epigenéticos, tales como la metilación del ADN, son sensibles a los comportamientos de prestaciones de cuidado y por consiguiente a la reactividad al estrés por parte de los hijos. Examinamos los efectos directos que los comportamientos de prestaciones de cuidado tienen sobre la metilación de ADN en infantes y, por consiguiente, la reactividad del estrés infantil. Los infantes y sus madres (N = 128) fueron evaluados durante una sesión de juego libre cuando los infantes tenían 5 meses de edad. Se codificó la sensibilidad materna y la apropiada forma de tocar y se obtuvo muestra de las células epiteliales bucales del infante para analizar la metilación de ADN del gen receptor glucocorticoide, NR3c1, exón 1F. Se evaluó la reactividad del infante al cortisol como respuesta al paradigma de la cara quieta. Niveles mayores de sensibilidad materna y apropiada forma de tocar se relacionaron con menos metilación de ADN de regiones específicas en NR3c1 exón 1F, aunque sólo en las niñas. No se presentó ninguna asociación con la sensibilidad materna y la apropiada forma de tocar, o metilación de ADN de NR3c1 exón 1F en el cortisol pre‐estrés o la reactividad del cortisol. Nuestros resultados se discuten en relación con modelos de programación que implican cuidado materno como un importante factor en la programación de la reactividad del estrés del infante. RÉSUMÉ: Les personnes prenant soin des enfants jouent un rôle critique dans l'échafaudage de la réaction au stress du nourrisson et la régulation mais les mécanismes selon lesquels cet échafaudage se bâtit ne sont pas clairs. Les modèles animaux suggèrent fortement que des processus épigénétiques, comme la méthylation de l'ADN, sont sensibles au comportements de qui prend soin d'eux et en conséquence déclenchent un réaction au stress. Nous avons examiné les effets directs des comportements soignants sur la méthylation de l'ADN chez les bébés, en ensuite sur la réaction au stress du nourrisson. Des nourrissons et leurs mères (N = 128) ont été évalués au moyen d'un jeu libre quand les bébés avaient 5 mois d'âge. La réaction maternelle et le toucher approprié ont été codés et des cellules épithéliales buccales du bébé ont été prélevées afin d'évaluer la méthylation de l'ADN du gène récepteur glucocorticoïde, le NR3c1 exon 1F. La réaction du cortisol du bébé a été évaluée en réponse au paradigme du visage immuable. Des niveaux plus élevés de réaction maternelle et de toucher approprié étaient liés à une méthylation de l'ADN des régions spécifiques de NR3c1 exon 1F moindre, mais seulement chez les filles. On n'a trouvé aucun lien avec la réaction maternelle et le toucher approprié ou de méthylation NR3c1 exon 1F de l'ADN sur le cortisol pré‐test ou de réaction du cortisol. Nos résultats sont discutés en relation aux modèles de programme qui impliquent que le soin maternel en tant que facteur important dans la programmation de la réaction au stress du bébé. ZUSAMMENFASSUNG: Die Bezugspersonen spielen eine entscheidende Rolle für die Herausbildung der Reaktionsfähigkeit und Regulierung von Säuglingen, aber die Mechanismen, wie diese entstehen, sind unklar. Tiermodelle deuten stark darauf hin, dass epigenetische Prozesse, wie z.B. die DNA‐Methylierung, sensitiv auf das Verhalten der Bezugspersonen reagieren und wiederum die Reaktivität der Nachkommen beeinflussen. Wir untersuchten die direkten Auswirkungen des Verhaltens der Bezugspersonen auf die DNA‐Methylierung bei Säuglingen und damit wiederum auf die Stressreaktivität von Säuglingen. Säuglinge und Mütter (N = 128) wurden während eines freien Spiels im Alter von 5 Monaten beurteilt. Die mütterliche Responsivität und die entsprechende Berührung wurden kodiert und bukkale Epithelzellen von Säuglingen wurden untersucht, um die DNA‐Methylierung des Glukokortikoid‐Rezeptorgens NR3c1‐Exon 1F zu beurteilen. Die Reaktivität des Säuglings auf Cortisol wurde als Antwort auf das Still‐Face‐Paradigma bewertet. Ein höheres Ausmaß an mütterlicher Responsivität und passenden Berührungen waren mit einer geringeren DNA‐Methylierung bestimmter Regionen im NR3c1‐Exon 1F verbunden, jedoch nur für das weibliche Geschlecht. Es gab keinen Zusammenhang für die mütterliche Responsivität und passende Berührungen oder DNA‐Methylierung des NR3c1‐Exons 1F mit der Reaktivität von Cortisol oder dem Cortisol vor der Belastung. Unsere Ergebnisse werden in Bezug auf Programmiermodelle diskutiert, die die mütterliche Fürsorge als einen wichtigen Faktor bei der Programmierung der Stressreaktivität von Säuglingen beinhalten. 抄録: 乳幼児期のNR3c1のＤＮＡメチル化:母親の養育と乳幼児の性別の関連 養育者は乳幼児のストレス反応性と調節の土台に大切な役割を果たすが、この土台が生じるメカニズムは明らかでない。動物モデルはＤＮＡメチル化のような、養育行動や、子どものストレス反応性に敏感である後成的なプロセスを強く示唆する。我々は養育行動が乳幼児のＤＮＡメチル化と、乳幼児のストレス反応性に直接与える影響を検討した。乳幼児が 5 ヶ月のとき、乳幼児と母親 （N=128） を自由遊び中に評価した。母親の応答性と適切な接触をコード化し、糖質コルチコイド受容体遺伝子である NR3cI エクソン 1F の DNA メチル化を評価するために乳幼児の頬粘膜細胞を標本抽出した。乳幼児のコルチゾール反応性は still face の反応性パラダイムに応じて評価した。より大きなレベルの母親の反応性と適切な接触は、 NR3cI エクソン 1F の特定領域の DNA メチル化に関連が少なかったが、それは女児だけにあてはまった。母親の反応性と適切な接触もしくは NR3cI エクソン 1F の DNA メチル化と、ストレス前のコルチゾールやコルチゾール反応性との関連は認めなかった。我々の研究結果を母親の養育が、乳幼児のストレス反応性のプログラミングにおける重要な因子であると示唆するプログラミングモデルとの関連から議論する。 摘要: 嬰兒期NR3c1的DNA甲基化:母親照顧與兒童性別的關係 護理人員在支架嬰兒對壓力反應和調節方面發揮著關鍵作用， 但這種支架發生的機制尚不清楚。動物模型強烈表明， 表觀遺傳過程， 如 DNA 甲基化， 對護理行為和後代壓力反應敏感。我們檢查護理行為對嬰兒 DNA 甲基化的直接影響， 進而檢測嬰兒對壓力反應。當嬰兒 5 個月大時， 在自由遊戲期間評估嬰兒和母親 （N = 128）。對母體反應性和適當的觸覺進行編碼， 並對嬰兒頰上皮細胞進行取樣， 以評估糖皮質激素受體基因 NR3c1 外顯子 1F 的 DNA 甲基化。評估嬰兒皮質醇反應性以響應靜止面觀範例。較高水平的母體反應性和適當的觸覺， 與 NR3c1 外顯子1F中特定區域的較少 DNA 甲基化相關， 但僅限於女嬰。母親反應和適當接觸或 NR3c1 外顯子 1F 的 DNA 甲基化， 與壓力前皮質醇或皮質醇反應性無關。我們討論結果與編程模型的關係， 這些編程模型將孕產婦護理作為影響嬰兒對壓力反應的重要因素。 ملخص: ميثيل الحمض النووي ل NR3c1 في مرحله الرضاعة: الارتباطات بين رعاية الامومة وجنس الرضع مقدمو الرعاية يلعبون دورا حاسما في تدعيم استجابة الرضع للإجهاد والتنظيم ولكن الآليات التي يحدث بها هذا التدعيم غير واضحة. النماذج الحيوانية تشير بقوة إلى ان العمليات الوراثية ، مثل ميثيل الحمض النووي ، حساسة لسلوكيات الرعاية وبدورها تولد الاستجابة التفاعلية للإجهاد العصبي. درسنا الآثار المباشرة لسلوكيات الرعاية علي ميثيل الحمض النووي في الرضع وكذلك الاستجابة التفاعلية للرضع. وتم تقييم الرضع والأمهات (العدد = 128) اثناء اللعب الحر عندما كان عمر الرضع 5 أشهر. وتم ترميز الاستجابة الاموميه واللمس المناسب وعينت الخلايا الظهاريه للرضع لتقييم ميثيل الحمض النووي من الجينات مستقبلات جلوكورتيكويد ، NR3c1 اكسون 1F . وتم تقييم تفاعل الكورتيزول للرضع استجابه لنموذج الوجه الثابت. وكانت المستويات الأكبر من الاستجابة الاموميه واللمس المناسب مرتبطة بمستوى أقل من ميثيل الحمض النووي في مناطق محدده في NR3c1 اكسون 1F ، ولكن فقط للإناث. ولم يكن هناك ارتباط مع استجابه الام واللمس المناسب أو ميثيل الحمض النووي من NR3c1 اكسون 1F علي الكورتيزول قبل الإجهاد أو الاستجابة التفاعلية للكورتيزول. وتناقش نتائجنا فيما يتعلق بنماذج البرمجة التي تضع رعاية الامومه كعامل مهم في برمجه استجابة الرضع التفاعلية للإجهاد العصبي.